The supergene mineral association with brandholzite from Pernek, Male Karpaty Mountains, Slovak Republic - Sejkora,J.; Ozdin,D.; Duda,R. (Journal of Geosciences, 2010)
Brandholzite, a hydrated hydroxide of Mg2+ and Sb5+, was found at the Kriznica deposit near Pernek (Male Karpaty Mountains, Slovak Republic); it is the third occurrence of this mineral phase worldwide. Crystals and crusts of brandholzite occur as surface coatings on altered shales mineralized with stibnite and pyrite. Associated minerals include romeite-like phases, sulphur, aragonite, gypsum, senarmontite and Sb-rich Fe-hydroxides. Brandholzite forms euhedral tabular crystals of hexagonal habit, typically 0.5 to 0.8 mm across, exceptionally up to 2 mm long. The crystals occur as isolated, or in randomly grouped individuals, creating inconspicuous crusts up to several cm2. Brandholzite crystals are colourless, transparent or showing white clouding. No fluorescence was observed under either short- or long-wave UV radiation. The average electron microprobe analysis gave 6.11 MgO, 0.52 CaO, 0.16 FeO, 55.89 Sb2O5, (37.32) H2O if recast to 100 wt. %. The calculated formula is (Mg0.88Ca0.05Fe0.01)Σ0.94(H2O)6.00[Sb(OH)6]2.00. The XRD pattern was indexed in a trigonal setting (space group P3), with refined unit-cell parameters a = 16.1076(9), c = 9.8628(9) Å and V = 2216.1(2) Å3. The thermogravimetric curve shows total weight loss of 34.6 wt. % (over the interval of 20-800 °C), caused by H2O release. The initial rapid weight decrease (20-140 °C) was followed by a minor continuous weight loss up to 800 °C. Brandholzite from Pernek and its mineral association were probably formed by sub-recent weathering processes in an abandoned mines environment.
Keywords: brandholzite; romeite; supergene mineral association; Pernek; Slovak Republic